Comprehensive Review of Anesthesia Monitoring Systems and Radiological Tools in Complex Surgical Interventions - Al-Zamanan, Hussain Manaa Zaid; Alarjani, Badryiah Mujhar Hadi; Al Rapaiyei, Fahad Saed Mahdi; Alshagaih, Bander Naseer; Al Monajam, Nova Yahya; AlShehri, Shohrah Abdurhman; Al Omar, Manal Mubarak; Al Omar, Afrah Mubarak; Al bleeh, Sheikha Saleh Hassan; Alsaad, Randa Saeed Samer; Elhussein, Musaab Abdalla (Journal of Ecohumanism, 2024)
The results of extremity revascularization depend remarkably on the application of modern anesthesia control devices and radiological equipment. They also protect the patients – both from themselves and potential infection – and maximize the accuracy of surgery and recovery times. Anesthesia monitoring systems give immediate information concerning patients’ condition, allowing anesthesiologists to alter settings for depth of anesthesia, control effects, and respond to alterations promptly. Most radiological technologies are diagnostic rather than therapeutic. Still, whether invasive or non-invasive, they help the surgeon portray the surgical area, and this is very crucial in planning surgeries, especially using minimally invasive methods. It aims to understand better how these technologies can work in combination, how efficient they are in enhancing the results of surgery, and the main issues associated with their application. Moreover, the work focuses on the continued developments in both disciplines while presenting the readers with an understanding of how both are changing the current surgical practices.